Automatic Voltage Restorer for Farm Motor - Rudhra, S.; Vinod, S.; Prakash, J. Arul; Kumar, M. Jagadeesh (2022 International Conference on Computer, Power and Communications (ICCPC), 2022)
This paper is to create and put into use an Automat-ic Voltage Regulator (AVR) with greater accuracy. In Tamil Nadu TNEB (Tamil Nadu Electricity Board) AC power supply is fre-quently subject to fluctuate in rural regions. Furthermore, supply voltage in rural regions continues to be lower than required. The complex electronic devices, such computers, refrigerators, and tele-visions, are severely threatened by voltage fluctuate. Therefore, it has become essential in both rural and certain metropolitan regions to ensure that the input voltage stays within a reasonable pre-specified level. Locally accessible solutions now lack precision and have the issue of cycling between two output voltages, which results in surges at the output that can harm priceless electronics. This paper propose a voltage controlling method for both voltage fluctu-ation in rural regions and low voltage issues. The servo operated transformer is introduced to bring the voltage within acceptable range of 215 to 235volts.